(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Electrical power distribution systems often face challenges due to environmental disturbances and delayed fault detection. This paper presents an Overhead AC Line Fault Detection and Monitoring System for improving safety and reliability. The system uses an ESP32 microcontroller integrated with IoT technology for real-time monitoring. It continuously observes voltage levels across multiple AC poles to detect faults and abnormalities. Temperature and flame sensors are used to monitor battery health and detect fire hazards. Sensor data is processed using embedded programming with predefined threshold values. In case of faults, the system generates instant alerts and updates the IoT cloud platform. An automatic cooling mechanism using a DC fan prevents overheating conditions. The ESP32 enables wireless data transmission for remote monitoring and quick response. The system reduces downtime, manual inspection, and improves operational efficiency. Overall, the solution is cost-effective, scalable, and suitable for modern power distribution networks.